IMPROVED GAS MIGRATION CONTROL IN OIL WELL CEMENT - ABBAS, GHULAM (2013)
Polymers are being used as multifunctional additives that control fluid loss, free water and prevent gas migration through cement slurry. Most ofthe polymers degrade at 80 °C and lose their viscosity with increasing temperature. The reduction in the viscosity of polymers leads to fluid loss, free water separation and decreases hydrostatic pressure which causes gas migration. In this research, Hydroxypropylmethylcellulose (HPMC) has been studied and used in cement slurry to prevent gas migration. The objectives of this study were to determine the viscosity of HPMC solutions, API properties and gas migration of HPMC based cement slurries at 90 °C. The viscosity of 1.5 and 2 wt% HPMC solutions was determined at different temperatures of 30 to 100 °C with respect to shear rates. The cement slurries of 16.5 ppg density were prepared using 0.20 to 0.80 gps concentration of HPMC solutions with fluid loss, dispersant, retarder and defoamer additives.